Thermal Intramolecular [2+2] Cycloaddition: Synthesis of 3‐Azabicyclo[3.1.1]heptanes from Morita–Baylis–Hillman Adduct‐Derived 4, 4‐Diaryl‐1, 3‐dienes. Issue 16 (16th October 2014) - Kim, Ko Hoon; Lim, Jin Woo; Lee, Junseung; Go, Min Jeong; Kim, Jae Nyoung
Abstract Various 3‐azabicyclo[3.1.1]heptane derivatives were synthesized from Morita–Baylis–Hillman adduct‐derived 1, 3‐dienes bearing a 4, 4‐diaryl moiety through a thermal intramolecular [2+2] cycloaddition approach. By using the same approach, bicyclo[3.1.1]heptane, 3‐azabicyclo[3.2.0]heptane, and 3‐oxabicyclo[3.1.1]heptane derivatives could also be synthesized. A structurally similar dimethylallyl derivative underwent an intramolecular ene reaction to afford the pyrrolidine derivative. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>